The Effect 0f Cerdas Learning Model on the Result of Students’ Natural Science - Noviani, Ketut Ari; Agustiana, I Gusti Ayu Tri (International Journal of Elementary Education, 2020)
The problem of this research was the lack of teachers in using innovative learning that affects studens’t learning outcomes. This research aimed to determine the effect of the “CERDAS" learning model on students’ natural science learning outcomes. The type of this research was a quasi-experimental research with a Post-test Only Control Group Design. The population of this research was all 128 students who were spread into eight schools. The sampling technique used in this research was the intact group random sampling technique. Based on the lottery technique, the results on fourth grade students of SDN 1 students were obtained as a control group and SDN 2 studnets as an experimental group consisted of 43 studnets. The method of data collection was done by a test method with a multiple choice test learning instrument in the form of 40 questions. T-test was used in this research. The results showed that there was an effect of the SMART learning model on the learning outcomes on the fourth grade natural science students in elementary school. This was indicated by the average score of the science learning outcomes test of the experimental group students was higher than the control group and the results of the t-test. So it can be concluded that the CERDAS learning model had a positive effect on the learning outcomes on fourth grade natural science students.